2013
DOI: 10.1089/end.2012.0637
|View full text |Cite
|
Sign up to set email alerts
|

Combined Low-Frequency Ultrasound and Microbubble Contrast Agent for the Treatment of Benign Prostatic Hyperplasia

Abstract: Background and Purpose: Benign prostatic hyperplasia is one of the most common conditions in middle-aged and elderly men. The aim of the study was to investigate the treatment effects of low-frequency ultrasound combined with a microbubbles agent on benign prostatic hyperplasia. Methods: Eighteen 7-year-old male beagles with prostatic hyperplasia were randomly divided into six groups (n = 3): Control group, 21 kHz ultrasound group, 21 kHz ultrasound and microbubble contrast agent group, 1 MHz ultrasound group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It has previously been reported that ultrasound combined with microbubbles induces cavitation, resulting in mitochondrial damage and subsequently mitochondria-dependent cell apoptosis (44,45). Cavitation is associated with inducing the opening of the mitochondrial permeability transition pore (44).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that ultrasound combined with microbubbles induces cavitation, resulting in mitochondrial damage and subsequently mitochondria-dependent cell apoptosis (44,45). Cavitation is associated with inducing the opening of the mitochondrial permeability transition pore (44).…”
Section: Discussionmentioning
confidence: 99%
“…However, other researches clearly proved that combined low-ultrasound microbubbles without payload can harmed cells and even be used as a treatment approach to cure diseases. S. Yang et al investigated this treatment effects on benign prostatic hyperplasia and observed serious tissues injury and cell apoptosis at only 21 kHz with combined ultrasound microbubbles compared to ultrasound and microbubbles separately [31]. In addition, preventive measures should be taken into consideration when correlating in vitro ultrasound parameters to in vivo conditions.…”
Section: Ultrasound Triggered Releasementioning
confidence: 99%